Monitoring of Ionosphere and Magnetosphere Plasma and High Energy Charge Particle Fluxes in Multi-satellite Measurements in Wide Range of Altitudes - Osedlo Vladislav (EDP Sciences, 2021)
A system for monitoring the radiation parameters of near-Earth space is described. This system is based on the multi-satellite measurements made on spacecraft Meteor, Electro, Arktika launched into orbits with a wide range of altitudes. The main instrument for space radiation monitoring is spectrometer of electrons and protons SKIF. Such instruments operate in all spacecraft of mentioned above series. The results of observations of different events connected with solar and geomagnetic activity in 2017 and 2021 years are presented and discussed.